Capital intelectual, capacidade absortiva e capacidade de inovação em empresas de base tecnológica do estado de Santa Catarina - Brasil - Bongiolo, Rafael Bavaresco (2019)
This research aimed to verify the relationship between intellectual capital, absorptive capacity and incremental and radical innovation capacity in technology-based companies. The study covered 407 company managers, including different segments and sizes, located in the state of Santa Catarina - Brazil. Methodologically, the research is characterized as quantitative, the data were collected through a questionnaire and the constructs and the theoretical model were confirmed through the Structural Equation Modeling. The results showed that human, structural and relational capital (intellectual capital) are positively related to the ability of companies to acquire and assimilate knowledge (potential absorptive capacity) and to transform and apply knowledge (realized absorptive capacity), at different levels of intensity. Relational capital was more strongly associated with absorptive capacity, both potential and realized, followed by structural capital and human capital. There was a strong effect of potential absorptive capacity on the realized absorptive capacity. In turn, potential absorptive capacity has a direct effect on incremental innovation capacity, but without the complementarity with realized absorptive capacity, it has no effect on radical innovation capacity. This complementarity not only contributes to the ability of companies to generate radical innovations, but also strengthens their ability to generate incremental innovations. The study contributes scientifically by involving the three constructs in a poorly explored sector - technology. Research can assist managers of technology-based companies in defining innovation-oriented policies and strategies, as it identifies resources and capabilities that contribute to the generation of incremental and radical innovations in this context, as well as the intensity of this contribution.